2020
DOI: 10.3390/cells9102258
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Sense Free Fatty Acids and Regulate Hepatic Lipid Metabolism in High-Fat Diet and Inflammation

Abstract: A high fat Western-style diet leads to hepatic steatosis that can progress to steatohepatitis and ultimately cirrhosis or liver cancer. The mechanism that leads to the development of steatosis upon nutritional overload is complex and only partially understood. Using click chemistry-based metabolic tracing and microscopy, we study the interaction between Kupffer cells and hepatocytes ex vivo. In the early phase of steatosis, hepatocytes alone do not display significant deviations in fatty acid metabolism. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…Indeed, Nakamoto et al used plain DHA (50 μL/day) [ 53 ], whereas in the present study, 4E% soybean oil was added to the FFC diet. Somewhat surprisingly, levels of plasma FFA were similar between groups, contrasting the findings of others in settings of diet-induced NAFLD in rodents [ 56 ]. However, in line with our findings, results of others also suggest that in the absence of abnormal weight gain and overweight, levels of FFA in plasma of mice fed a high-fat and high-sugar diet remain unchanged [ 57 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Indeed, Nakamoto et al used plain DHA (50 μL/day) [ 53 ], whereas in the present study, 4E% soybean oil was added to the FFC diet. Somewhat surprisingly, levels of plasma FFA were similar between groups, contrasting the findings of others in settings of diet-induced NAFLD in rodents [ 56 ]. However, in line with our findings, results of others also suggest that in the absence of abnormal weight gain and overweight, levels of FFA in plasma of mice fed a high-fat and high-sugar diet remain unchanged [ 57 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Notably, apart from KCs being the main drivers of inflammation in NASH, they may also directly drive steatosis development, as KC depletion in rats has been shown to prevent HFD-induced steatosis [ 230 ]. In further support of this notion, in a HFD NAFLD model, LPS or FFA-driven activation of KCs mediated steatosis formation in hepatocytes via tumor necrosis factor signaling [ 231 ].…”
Section: Dysregulation Of Autophagy and Lipid Droplet Function In Non...mentioning
confidence: 99%
“…Various cell types are involved in the occurrence of AFL, such as hepatocytes, immune cells and HSCs. Among them, Kupffer cells was the most widely studied, which caused in ammation, liver damage and fatty liver by secreting a large number of in ammatory cytokines such as TNF-α, IL-1 and IL-17 [50]. In addition, it had also been found that HSCs not only played a role in the development of liver brosis by secreting extracellular matrix, but also promoted lipogenesis by secreting factors such as endocannabinoids.…”
Section: Discussionmentioning
confidence: 99%